The role of curriculum evaluation in quality education in Nigeria (2011)
The paper dwelt on the role of Curriculum Evaluation in quality education in Nigeria. The quality of education in Nigeria has come under serious criticism in recent years. The paper revealed that credence has been lent more to these criticisms because of the poor performance of students noticed in public examinations like the West African School Certificate Examination (WASCE) and the National Examination Council (NECO). As a result of these fall out, the effectiveness of public secondary school in Nigeria has become an issue of debate. The paper stated that, since curriculum evaluation is the act of gauging the value and effectiveness of any aspect of educational activities, it then becomes imperative to look at certain aspects of the Secondary School System in Nigeria, especially the teaching learning process. The paper goes further to explain how curriculum evaluation may come handy in solving some of the problems facing secondary school education in Nigeria, such as, issues bothering on instructional methods, instructional materials, class size, students' assessment and evaluation and other sundry issues affecting quality education in Nigeria. The paper concluded that mass failure in public examination can be drastically reduced in Nigeria if curriculum evaluation is allowed to thrive within the educational system in the country.